Systematization of experiences: Use of an analysis guide of the film Soul in vocational guidance processes for the process of career change or reaffirmation in a university population. (Costa Rican Journal of Guidance & Counseling, 2023)
This systematization brings together the experience related to the construction and implementation of an analysis guide for the film Soul, with the aim of accompanying vocational orientation processes, with the student population of the Social Sciences area at the University of Costa Rica.It is for the above that the objective of this experience is to document the creation and implementation of an innovative qualitative tool in the field of vocational guidance with the university population. This experience is based on the individual accompaniment carried out to seven students during the year 2021, whose subject of attention was related to the change or reaffirmation of their university career.Following the steps of the methodological process of a systematization of experiences, for the reconstruction of the history and analysis, the professional annotations resulting from each intervention, the written responses from people about the use of the guide and the electronic records of the Individual Attention System of the Guidance Office were used.Based on this information, conclusions and recommendations are made both to the experience in the use of the guide, and to the course of systematization of experiences offered by the College of Guidance Professionals, which makes the creation of the document possible.
Keywords: vocational guidance; qualitative tools for vocational exploration; individual attention; career reaffirmation; career change